Development and evaluation of the remote passive integrated transponder tag reader for customizable monitoring of wildlife - Staci M. Amburgey; Aadithya Prakash; Amy A. Yackel Adams; Shane R. Siers; Sarah J. Converse (Wildlife Society Bulletin)
Abstract Increasing the quantity and quality of mark‐reencounter data can be important when individual identification data are needed to address research or management questions. Physical recapture methods tend to be labor‐intensive and therefore expensive, while remote detection methods are not easily applied to all taxa or are proprietary and thus difficult to customize. However, partnerships between wildlife scientists and engineers have the potential to provide innovative solutions that improve data collection while reducing costs. We describe a collaborative effort to improve the collection of mark‐reencounter data on an invasive reptile, the brown treesnake (Boiga irregularis). In laboratory trials conducted on Guåhan (CHamoru; Guam in English) in 2021, we assessed the feasibility of detecting snakes fitted with passive integrated transponder (PIT) tags using customized remote PIT‐tag readers (RePTaR) paired with baited snake traps. We evaluated differences in scanning success as a function of snake traits, location of PIT tags within snakes, and the distance of the PIT tag from the reader. We successfully scanned all individuals, on average 529 times but ranging from 3 to 6,436 times, during 12‐hour trials using a designed customizable RePTaR unit. Snake characteristics and marking location explained little of the variability in scanning success, with distance from the reader as the best‐supported covariate. By building cross‐disciplinary partnerships, we can develop customizable technological solutions and provide additional tools with which to address challenges in wildlife research and management.